Evaluation of 1, 2-O-dilauryl-rac-glycero glutaric acid-(6′-methylresorufin) ester (DGGR) and 1, 2-diglyceride lipase assays in dogs with naturally occurring hypercortisolism. (September 2021) - Linari, Guido; Dondi, Francesco; Segatore, Sofia; Vasylyeva, Kateryna; Linta, Nikolina; Pietra, Marco; Leal, Rodolfo O.; Fracassi, Federico
1, 2-O-dilauryl-rac-glycero glutaric acid-(6′-methylresorufin) ester (DGGR) lipase activity has been proposed as a faster and less expensive test used in the diagnosis of acute pancreatitis (AP) compared to canine pancreatic lipase immunoreactivity (cPLI), which is considered the most sensitive and specific serum test available for dogs. Elevations in lipase activity have been observed in dogs with naturally occurring hypercortisolism (HC) and in those treated with exogenous steroids, which complicates the diagnosis of AP in dogs with HC. We compared lipase activity measured by DGGR and 1, 2-diglyceride (1, 2-DiG) assays in 22 dogs with HC, 22 with AP, and 22 healthy dogs. The dogs with HC had no clinical signs or ultrasonographic findings consistent with AP. DGGR lipase activity was elevated in 64% and 73% of the dogs with HC and AP, respectively, and in 18% of healthy dogs. 1, 2-DiG lipase activity was high in 23% and 36% of the dogs with HC and AP, respectively, and in 5% of the healthy dogs. Both DGGR and 1, 2-DiG lipase activities were significantly different between the healthy dogs and the other 2 groups, whereas no differences were detected between the dogs with HC and those with AP. Our results support a lack of specificity for both DGGR and 1, 2-DiG lipase activity assays in aiding the diagnosis of AP in dogs with HC.